Use of Carnosine for Oxidative Stress Reduction in Different Pathologies. (24th January 2016) - Prokopieva, V. D.; Yarygina, E. G.; Bokhan, N. A.; Ivanova, S. A.
Abstract : The main properties and biological effects of the antioxidant carnosine, the natural dipeptide β -alanyl-L-histidine, are considered. Data on the effective use of carnosine in different pathologies are presented. Special attention is paid to issues of use of carnosine in neurologic and mental diseases, in alcoholism as well as in physiological states accompanied by activation of free-radical processes and formation of oxidative stress.